Synopsis of systematic reviews on the clinical effect of Ketamine in the agitated patient - Berrouet-Mejía, Marie Claire; Moreno-Quimbay, Sebastián; Cardona, Jaiberth; Patiño-Ospina, Alber Johnny (Universidad y Salud, 2023)
Introduction: The scientific literature about Ketamine use shows high heterogeneity in terms of design, populations, outcomes, and clinical specialties. Nevertheless, available evidence systematically consolidated to guide clinical decisions for anxious patients was not found. Objective: To analyze evidence available in systematic reviews about the use of Ketamine in anxious patients. Materials and methods: Systematic search in multidisciplinary databases. The “A measurement Tool to Assess Systematic Reviews-2” was used to guarantee comprehensiveness of the searching protocol and study selection, reproducibility, and analysis of the methodological quality. A quantitative synthesis of the extracted variables and proportion estimation with a 95% CI were performed. Results: 10 out of 134 screened studies met the protocol criteria. The systematic reviews included a population of 26,936 patients and the evidence comes mainly from two case series, 7 observational studies, and 9 controlled clinical trials. Ketamine has multiple adverse effects, some of them more critical than those caused by Midazolam. Conclusion: Some patient subgroups showed a high frequency of adverse effects such as respiratory, neuropsychiatric, and cardiovascular dysfunctions, but it was difficult to generalize them to other contexts. It is necessary to improve clinical and epidemiological evidence in order to prescribe Ketamine to manage anxiety.